IMPROVING ABILITY READ THROUGH MEDIA of MATCHING BOARD TO CHILD DIFFICULTY LEARN - Yudi Alfisah (Universitas Negeri Padang, 2014)
Abstrack: This research is motivated by problems in children researchers found difficulty child learn to read X class III SDN 19 Kapalo Koto Padang can not the reading. This study aims to improve children's reading skills for difficulty child learn to read. This research is a single research subject (SSR). This study used a design A-B-A. Matching board results showed to be effective in improving reading skills for children at SDN 19 Kapalo Koto Padang difficulty child learn to read. Kata kunci: Membaca, matching board, anak kesulitan belajar membaca.